2004
DOI: 10.1590/s0004-27302004000400016
|View full text |Cite
|
Sign up to set email alerts
|

Complexo de Carney: relato de um caso e revisão da literatura

Abstract: RESUMOComplexo de Carney (CNC) pode ser definido como uma forma de neoplasia endócrina múltipla familial associada a alteração de pigmentação cutânea e de mucosa, doença nodular pigmentosa primária das adrenais, mixomas cardíacos e cutâneos, adenomas hipofisários produtores de GH e PRL, neoplasia testicular, adenoma ou carcinoma de tireóide, além de cistos ovarianos. CNC tem herança autossômica dominante e possui manifestações clínicas que são, em alguns aspectos, similares às da síndrome de McCune-Albright. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
6
0
4
Order By: Relevance
“…In studies on autopsies of patients with CNC, PPNAD was observed in almost all cases. 4,10,11 Although our patient presented a classical picture of Cushing's syndrome, her two-year history of amenorrhea, which was thought to have been caused previously by PCOS, and her short stature could be indicative of a disease that emerged atypically a long time earlier.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In studies on autopsies of patients with CNC, PPNAD was observed in almost all cases. 4,10,11 Although our patient presented a classical picture of Cushing's syndrome, her two-year history of amenorrhea, which was thought to have been caused previously by PCOS, and her short stature could be indicative of a disease that emerged atypically a long time earlier.…”
Section: Discussionmentioning
confidence: 77%
“…7,11 Paradoxical cortisol secretion responses after performing the Liddle test (two days of baseline collection, two days of dexamethasone 0.5 mg orally every six hours followed by two days of 2 mg orally every six hours and a new sample on the sixth day of the test) showed an increase of more than 50% in 24-hour urinary free cortisol (UFC) in relation to the baseline value. This is considered to be one of the major criteria for CNC.…”
Section: Discussionmentioning
confidence: 99%
“…In general, osseous alterations found in CNC patients are a consequence of associated hypercortisolism. Thus, because PTH signaling also depends on PKA activation, the osseous metabolism alterations found in CNC patients can also be related to the excessive action of this hormone (2). In this case report the patient presented increased calcium and PTH intact after surgery, but these parameters subsequently normalized.…”
Section: Supplemental Criteriamentioning
confidence: 72%
“…Loss of PKA regulatory subunits increases its catalytic activity, providing cellular proliferation in various tissues, which results in endocrine hyperfunction and the development of neoplasias. They are germ mutations, in heterozygosis, resulting from an unexpressed allele, which leads to haploinsufficiency (2). On the other hand, in MEN1 the causative gene, located in the 11q13 chromosome, consists of 10 exons and encodes a protein, composed of 610 amino acids, called menin (3,5).…”
Section: Supplemental Criteriamentioning
confidence: 99%
See 1 more Smart Citation